Scaling Up Programmatic Management of Drug-Resistant Tuberculosis: A Prioritized Research Agenda - Cobelens, Frank G. J; Heldal, Einar; Kimerling, Michael E; Mitnick, Carole D; Podewils, Laura J; Ramachandran, Rajeswari; Rieder, Hans L; Weyer, Karin; Zignol, Matteo (PLoS medicine, 2008)
Frank Cobelens and colleagues outline key research questions that need to be addressed to maximize the impact of programmatic management of drug-resistant tuberculosis.